(untitled) (Emancipação, 2025)
This article aims to analyze national results presented in the SUAS/2022 Census, regarding units that welcome children and/or adolescents. There are two types of units: (1) mixed, which welcome children and/or adolescents with or without disabilities and (2) exclusive, which exclusively accommodate children and/or adolescents with disabilities. This is a documentary and census research carried out based on a comparative study that investigated general characteristics of the units, human resources, forms of accessibility and the reception-school relationship using the integrated approach technique for data analysis. 2916 mixed units and 23 exclusive units were located across the country. Even with the advances in public policies achieved, the results reveal that the public found in exclusive units, in addition to being socially separated, did not obtain equal rights in relation to the general number of people welcomed, as recommended by legislation.